Building resilience through sustainable groundwater use - CGIAR Research Program on Water, Land and Ecosystems (International Water Management Institute, 2017)
Using groundwater for agricultural production has the potential to build resilience in food insecure regions of the world. Use of groundwater can boost agricultural production, improve rural incomes and strengthen farmers’ ability to withstand climate shocks and water variability. However, for groundwater to contribute to sustainable intensification of agriculture, it is essential to know where to invest in groundwater development and how to sustainably manage groundwater resources. WLE has identified potentially usable groundwater resources in Africa, supported important policy changes to enhance the sustainable use of groundwater in eastern India, and has developed maps and new tools that can be used to implement new policies supporting sustainable use of groundwater.